2021
DOI: 10.1002/ijc.33866
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acids in gynecological cancer development and progression: Impact on diagnosis and treatment

Abstract: Gynecological cancers are in the top 10 of most common cancers in women. Survival and outcome are strongly related to the stage at diagnosis. Therefore, early diagnosis is essential in reducing morbidity and mortality. The high mortality rate of gynecological cancers can mainly be attributed to ovarian cancer (OC). OC is commonly diagnosed at an advanced stage due to a lack of proper screening tools allowing early detection. Endometrial cancer (EC) on the contrary, is mostly diagnosed at an early stage and has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 95 publications
0
10
0
Order By: Relevance
“…22 It participates in the reprogrammed metabolisms of cancer cells, thus affecting cell adhesion, intercellular communication, and contact inhibition. 14,21 Under normal circumstances, the serum SA level remains stable. However, when cells undergo malignant transformation, SA is shed from the cell surface and circulates in the bloodstream as serum 23 In malignant tumor cells, there is an increase in SA synthesis metabolism, known as hypersialylation, which promotes tumor progression.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…22 It participates in the reprogrammed metabolisms of cancer cells, thus affecting cell adhesion, intercellular communication, and contact inhibition. 14,21 Under normal circumstances, the serum SA level remains stable. However, when cells undergo malignant transformation, SA is shed from the cell surface and circulates in the bloodstream as serum 23 In malignant tumor cells, there is an increase in SA synthesis metabolism, known as hypersialylation, which promotes tumor progression.…”
Section: Discussionmentioning
confidence: 97%
“…Our study showed that the high SA group had a lower LRRFS, DMFS, PFS, and OS, indicating that increased SA is a poor prognostic factor for tumors, correlating with the clinical activity of the disease, similar to conclusions from studies conducted on many cancer types. [13][14][15]25,26 Research has also shown that SA levels were higher in the group of patients with metastatic breast cancer compared to those with non-metastatic breast cancer. 27 Currently, chemoradiotherapy is the preferred treatment modality for NPC.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Targeting OC is of particular importance since patients with OC are reported to have significantly enhanced level of the total sialylation (α2,3-/ α2,6-linked Sia). The bi-and trisialylated highly branched glycans exhibit low expression in healthy individual, whereas they are reported to be overexpressed in patients with OC (14)(15)(16). The interaction between Siglec-7 and its ligands has been reported to play a role in the inhibition of NK-mediated antitumor toxicity (7).…”
Section: Introductionmentioning
confidence: 99%
“…Among pelvic tumors, cervical cancer, endometrial cancer, and ovarian cancer are among the top 10 most common cancers in women ( 1 ). Among these, ovarian cancer is considered to be a “silent killer”, as most patients present with few symptoms or are diagnosed at the advanced stages (III and IV) ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%